Influence of gender on loss to follow-up in a large HIV treatment programme in western Kenya - Vincent Ochieng-Ooko; Daniel Ochieng; John E Sidle; Margaret Holdsworth; Kara Wools-Kaloustian; Abraham M Siika; Constantin T Yiannoutsos; Michael Owiti; Sylvester Kimaiyo; Paula Braitstein (The World Health Organization, 2010)
OBJECTIVE: To determine the incidence of loss to follow-up in a treatment programme for people living with human immunodeficiency virus (HIV) infection in Kenya and to investigate how loss to follow-up is affected by gender. METHODS: Between November 2001 and November 2007, 50275 HIV-positive individuals aged > 14 years (69% female; median age: 36.2 years) were enrolled in the study. An individual was lost to follow-up when absent from the HIV treatment clinic for 3 months if on combination antiretroviral therapy (cART) or for 6 months if not. The incidence of loss to follow-up was calculated using Kaplan-Meier methods and factors associated with loss to follow-up were identified by logistic and Cox multivariate regression analysis. FINDINGS: Overall, 8% of individuals attended no follow-up visits, and 54% of them were lost to follow-up. The overall incidence of loss to follow-up was 25.1 per 100 person-years. Among the 92% who attended at least one follow-up visit, the incidence of loss to follow-up before and after starting cART was 27.2 and 14.0 per 100 person-years, respectively. Baseline factors associated with loss to follow-up included younger age, a long travel time to the clinic, patient disclosure of positive HIV status, high CD4+ lymphocyte count, advanced-stage HIV disease, and rural clinic location. Men were at an increased risk overall and before and after starting cART. CONCLUSION: The risk of being lost to follow-up was high, particularly before starting cART. Men were more likely to become lost to follow-up, even after adjusting for baseline sociodemographic and clinical characteristics. Interventions designed for men and women separately could improve retention.